Impact of financial development on agricultural productivity in South Asia - Muhammad Zakaria; Wen Jun; Marium Farrukh Khan (Agricultural Economics (AGRICECON), 2019)
The paper examines the impact of financial development on agricultural productivity in South Asia using data for the period 1973-2015. The other variables included are physical capital, human capital, trade openness and income level. It is found that all variables have cross-section dependence and they are stationary at first differences. It is found that long-run cointegration holds among variables. The estimated results show that financial development has an inverted U-shaped effect on agricultural productivity, which implies that agricultural productivity first increases with the increase in financial development and then it declines when financial development further increases. Agricultural productivity increases with the increase in both physical and human capitals. Agricultural productivity also improves with trade openness and income level. The results of the robustness analysis show that terms of trade has a negative effect on agricultural productivity. Further, industrialisation has positive while carbon emission and rural labour force have negative effects on agricultural productivity in the region.